Dragon Ball super. 4, Last chance for hope - Toriyama, Akira, 1955-2024 (Shonen Jump manga., 2019)
When Zamas and his counterpart from the parallel universe team up, they become nearly unstoppable, and Goku must train with Master Roshi to defeat them.